Ekosistem Halal sebagai Strategi Penguatan UMKM untuk Meningkatkan Pertumbuhan Usaha Berkelanjutan - Mahlel Mahlel (Yayasan Madinah Al-Aziziyah, 2026)
MSMEs play a crucial role in the economy, yet they require strengthening strategies that support genuinely sustainable business growth. Growing consumer demand for halal products has positioned halal not merely as a label but as a quality system that involves process standards, traceability, and governance. This article aims to address the knowledge gap on how a halal ecosystem functions as an integrated MSME-strengthening strategy, including which components matter most and how inter-component linkages operate in practice. The study applies library research, synthesizing academic literature and relevant documents on halal ecosystems, MSME strengthening, and sustainable growth. The review indicates that prior studies often discuss certification, mentoring, financing, supply chains, and market access as separate factors, while operational models that explain service flows and impact indicators remain limited. It also finds that program success is frequently measured through compliance and short-term market opportunities, whereas sustainability dimensions—such as business stability, consistent quality, and resilience—are less clearly operationalized. The study concludes that a halal ecosystem should be framed as a coordinated, adaptive, and measurable support system to effectively strengthen MSMEs. This article contributes by proposing an operational direction for mapping ecosystem mechanisms, component priorities, and impact measures that can inform implementation and future research.